Microsoft Office Training: Building Digital Skills of Students at Walisongo Ngabar Ponorogo Islamic Boarding School - Ratna Utami Nur Ajizah (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
Microsoft Office training at Walisongo Ngabar Islamic Boarding School, Ponorogo, is a strategic initiative to improve the digital skills of students. In the digital era that demands technological literacy skills, this training aims to equip students with basic competencies in the use of Microsoft Word, Excel, and PowerPoint. This study uses a qualitative descriptive approach with observation, interview, and documentation methods to measure the effectiveness of the training. This program is designed so that students are not only proficient in religious practices, but also ready to face the challenges of the world of work and higher education that demand digital skills. Training methods include direct learning, independent practice, and task-based evaluation. The results of the training showed a significant increase in understanding and skills in using office applications, especially in creating documents, managing data, and preparing presentations. In addition, this training encourages students to be more confident in using technology as a means of preaching and modern communication. This activity also strengthens the role of Islamic boarding schools as educational institutions that are adaptive to the development of the times. With the integration of digital training in the non-formal curriculum, students not only gain added value personally, but also contribute to increasing the competitiveness of the institution. This training is a model for developing soft skills that are relevant and applicable for the generation of students in the 21st century